Manajemen Berbasis Madrasah dalam Peningkatan Standar Kompetensi Lulusan Madrasah Aliyah - Budi Handrianto; Ahmad A Sastra; Dwi Sulaksana (UMSU, 2022)
The research was conducted using a qualitative method to determine the perception of madrasah-based management (MBM) in improving the competency standards of madrasah aliyah graduates from the Fatah Syukur book which was then measured and analyzed its principles and components through implementation at MAN Insan Cendekia Serpong which is currently the best madrasa aliyah in the world. Indonesia. In this study, it was found that through the application of MBM, madrasas will be able to again contribute to a superior level of human civilization. In which it is found that human qualities not only master science but also have the power of faith and piety and also have good life skills. In implementing this MBM, a strong political will is needed from madrasa managers and must make serious efforts so that madrasas can regain public trust in education management in order to achieve good graduate competency standards. But in its implementation the implementation of MBM itself still requires a strategic approach and also requires managerial dynamics to various educational problems, especially in the current digital age.